Surgical Satisfaction, Quality of Life, and Their Association After Gender-Affirming Surgery: A Follow-up Study. Issue 2 (17th February 2018) - van de Grift, Tim C.; Elaut, Els; Cerwenka, Susanne C.; Cohen-Kettenis, Peggy T.; Kreukels, Baudewijntje P. C.
ABSTRACT: We assessed the outcomes of gender-affirming surgery (GAS, or sex-reassignment surgery) 4 to 6 years after first clinical contact, and the associations between postoperative (dis)satisfaction and quality of life (QoL). Our multicenter, cross-sectional follow-up study involved persons diagnosed with gender dysphoria ( DSM-IV-TR ) who applied for medical interventions from 2007 until 2009. Of 546 eligible persons, 201 (37%) responded, of whom 136 had undergone GAS (genital, chest, facial, vocal cord and/or thyroid cartilage surgery). Main outcome measures were procedure performed, self-reported complications, and satisfaction with surgical outcomes (standardized questionnaires), QoL (Satisfaction With Life Scale, Subjective Happiness Scale, Cantril Ladder), gender dysphoria (Utrecht Gender Dysphoria Scale), and psychological symptoms (Symptom Checklist-90). Postoperative satisfaction was 94% to 100%, depending on the type of surgery performed. Eight (6%) of the participants reported dissatisfaction and/or regret, which was associated with preoperative psychological symptoms or self-reported surgical complications ( OR = 6.07). Satisfied respondents' QoL scores were similar to reference values; dissatisfied or regretful respondents' scores were lower. Therefore, dissatisfaction after GAS may be viewed as indicator of unfavorable psychological and QoL outcomes.